Associate Professor dr. Božidar Kert - a review of his professional career on his ninetieth anniversary - Kolnik, Karmen; Konečink Kotnik, Eva (Journal for Geography, 2018)
The article provides an analytical overview of the four areas of professional work of dr. Božidar Kert at his 90th anniversary. We presented his educational path, careers, research and pedagogical work, as he is one of the founders of the Maribor Geographical Department. Research basis of his bibliographic units, records of four long-time professional collaborators and semi-structured interviews of the celebrator. We also provided the analysis of the existing published and also his personal, unpublished materials.
Keywords: Božidar Kert; geography; interview; professional biography; bibliography